2022
DOI: 10.3390/ijms232113504
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Roots Response to Potassium Deficiency and the Effect of TaHAK1-4A on K+ Uptake in Wheat

Abstract: Potassium (K+) is essential for plant growth and stress responses. A deficiency in soil K+ contents can result in decreased wheat quality and productivity. Thus, clarifying the molecular mechanism underlying wheat responses to low-K+ (LK) stress is critical. In this study, a tandem mass tag (TMT)-based quantitative proteomic analysis was performed to investigate the differentially abundant proteins (DAPs) in roots of the LK-tolerant wheat cultivar “KN9204” at the seedling stage after exposure to LK stress. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…Under 10 µM KCl condition, MeHAK5 transgenic plants had better growth performance compared to WT plants, with higher biomass and shoot K + content and longer primary root lengths ( Figure 5 ), supporting the conclusion that HAK5 mainly functions in the range of 10–50 µM K + concentration [ 55 ]. These results are consistent with those in transgenic Arabidopsis plants overexpressing Ta HAK1-4A [ 62 ]. Thus, Me HAK5 functions in relation to high-affinity K + uptake under low potassium conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Under 10 µM KCl condition, MeHAK5 transgenic plants had better growth performance compared to WT plants, with higher biomass and shoot K + content and longer primary root lengths ( Figure 5 ), supporting the conclusion that HAK5 mainly functions in the range of 10–50 µM K + concentration [ 55 ]. These results are consistent with those in transgenic Arabidopsis plants overexpressing Ta HAK1-4A [ 62 ]. Thus, Me HAK5 functions in relation to high-affinity K + uptake under low potassium conditions.…”
Section: Discussionsupporting
confidence: 91%
“…HbHAK1 expressed in the yeast mutant CY162 exhibited a strong K + uptake capacity under extreme K + deficiency [ 41 ]. Furthermore, both wheat Ta HAK1-4A and Casuarina equisetifolia Ceq HAK6 have recently been shown to participate in high-affinity K + uptake under K + -deficient conditions [ 49 , 62 ]. In this study, MeHAK5 was expressed in the yeast mutant CY162.…”
Section: Discussionmentioning
confidence: 99%
“…K + channels and transporters are critical for the uptake of K + in wheat. For example, TaAKT1 contributes to the constitutive and inducible K + uptake by wheat roots [43], while TaHAK1-4A is important for the uptake of K + by LK-stressed wheat roots [44]. Another recent study indicated that TaHAK5 promotes wheat root elongation and K + uptake [45].…”
Section: Discussionmentioning
confidence: 99%